The situation of using artificial sweetener instead of sugar in instant beverage powder - โรจนวณิชชากร, อารยะ; หลวงพิทักษ์, ไพโรจน์; ช่างเจริญ, ธันย์ชนก; ศิริเวชยันต์, เสริมสกุล (Journal of Nutrition Association of Thailand (Online), 2017)
Non-Communicable Diseases (NCDs) have a tendency to increase among Thai people every year. One major cause of this issue is over-consumption of sugar, which is commonly found in instant beverage powder that contained a lot of sugar per serving. The purpose of this research is to obtain total sugar and artificial sweetener content in instant beverage powder available in Thailand.A survey was conducted in eight department stores, collecting 243 food and nutrition facts labeled of instant beverage powder. The average total sugar content was 9.92 ± 6.45 grams per serving. There were 69 products (28.39%) using sweeteners instead of sugar, which mostly found in coffee and tea instant beverage powder. A survey of 800 consumers by using online questionnaires found that 21 percent of consumers agreed with the use of artificial sweetener in order to reduce sugar content. Interviewing with 5 entrepreneurs found that most of the food producers had developed products using artificial sweeteners in the instant beverage powder products; however after taste and limited amount of artificial sweeteners added to the products were reported. The tendency of using artificial sweeteners as sugar substitution had continuously increased. Therefore, consumer should be educated to gain insight on how to consume artificial sweeteners safely.